(untitled) (Biological Sciences - PJSIR, 2007)
Regeneration of spent Cr+6 solutions usi ng lead dioxide anodes was i nvestigated. Pure and Cu+2 doped lead dioxide electrodes were prepared by electrodeposition of lead dioxide on carbon-based substrates using Pb+2 nitrate bath at 1.5-1.75 V, pH 4-4.5 , temperature 60-70 °C and current density 0.01 25-0 .0175 A/cm 2 . Electrol yses of prepared Cr+3 solutions, both i n divided and undi vided cells, were used to i nvestigate the electrocatalytic activity, adhesion and stabi l ity of lead dioxide electrodes, wh ich can serve as i nd ustrial electrodes. UV-visible spectrophotometr y was used for estimati ng conversion of Cr+ 3 to Cr+6 . The electrocatalytic acti vity of lead dioxide was increased by doping of Cu·’ ions.